From global factory to global mall: East Asia's changing trade composition - Matthias Helble; Boon-Loong Ngiang (Asian Development Bank Institute (ADBI), 2014)
This paper studies how East Asia's trade composition and orientation have changed over the past decade and analyzes the implications for the region and beyond. Over the last 2 decades we have witnessed the emergence of regional and global supply chains, in which production is divided into production stages or tasks across the most competitive locations. East Asia has been the most successful region in the world in building up or joining regional and global supply chains and has been described as "Factory Asia" (Baldwin 2008). Introducing a new and simple analytical tool, we show that over the past decade East Asia has successfully consolidated its role as the "Global Factory." Furthermore, studying East Asia's recent trade patterns in primary, intermediate, capital, and consumption goods, our results indicate that East Asia is on track to becoming one of the biggest "malls" in the world. Whereas in 1999 - 2000 around half of all consumption goods exported by East Asia went to the United States and the European Union-27, in 2011 - 2012 half stayed in the region or were traded with the rest of the world.
Keywords: F14; F15; N15; 330